DETERMINAN FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021: INDONESIA - Zulkarnain; Nurhayati; Heffi Christya Rahayu; Yulfita Aini (AKPEM : Jurnal Akuntansi Keuangan dan Pemerintahan, 2023)
The purpose of this study was to determine the effect of profitability, financial leverage, liquidity, company size, and managerial ownership on income smoothing in manufacture companies listed on the Indonesian stock exchange in 2019-2021. This study uses secondary data obtained from company financial reports for manufacture companies listed on the Indonesian stock exchange for 2019-2021.The method used is a quantitative method. The population in this study amounted to 192 companies and obtained a sample of 29 companies with a total of 87 data. The determinant factors that influence the practice of income smoothing in this study are profitability (X1), financial leverage (X2), liquidity (X3), firm size (X4) and managerial ownership (X5). The analytical method used is logistic regression analysis using the SPSS 25 application.The results of this study indicate that the financial leverage variable and company size variable has an effect on income smoothing, while profitability, liquidity and managerial ownership have no effect on income smoothing, and simultaneous profitability, financial leverage, liquidity, company size, and managerial ownershiphave an effect on income smoothing.